Reticular Formation and Pain: The Past and the Future - Martins, Isabel; Tavares, Isaura (Frontiers in Neuroanatomy, 2017)
The involvement of the reticular formation in the transmission and modulation of nociceptive information has been extensively studied. The brainstem reticular formation contains several areas which are targeted by spinal cord afferents conveying nociceptive input. The arrival of nociceptive input to the reticular formation may trigger alert reactions which generate a protective/defense reaction to pain. Reticular formation neurons located at the medulla oblongata and targeted by ascending nociceptive information are also involved in the control of vital functions that can be affected by pain, namely cardiovascular control. The reticular formation contains centers that belong to the pain modulatory system, namely areas involved in bidirectional balance (decrease or enhancement) of pain responses. It is currently accepted that the imbalance of pain modulation towards pain facilitation accounts for chronic pain. The medullary reticular formation has the peculiarity of harboring areas involved in bidirectional pain control namely by the existence of specific neuronal populations involved in antinociceptive or pronociceptive behavioral responses, namely at the rostroventromedial medulla (RVM) and the caudal ventrolateral medulla (VLM). Furthermore the dorsal reticular nucleus (also known as subnucleus reticularis dorsalis; DRt) may enhance nociceptive responses, through a reverberative circuit established with spinal lamina I neurons and inhibit wide-dynamic range neurons of the deep dorsal horn. The components of the triad RVM-VLM-DRt are reciprocally connected and represent a key gateway for top-down pain modulation. The RVM-VLM-DRt triad also represents the neurobiological substrate for the emotional and cognitive modulation of pain, through pathways that involve the periaqueductal gray-RVM connection. Collectively, we propose that the RVM-VLM-DRt triad represents a key component of the “dynamic pain connectome” with special features to provide integrated and rapid responses in situations which are life-threatening and involve pain. The new available techniques in neurobiological studies both in animal and human studies are producing new and fascinating data which allow to understand the complex role of the reticular formation in pain modulation and its integration with several body functions and also how the reticular formation accounts for chronic pain.